Flood early warning monitoring system and water depth limit in the Curug Dhuwur river tourist area, Bumisari Village - Fajar Setiawan; Aulia Desy Nur Utomo; Anggi Zafia (Institute of Computer Science (IOCS), 2026)
Waterfall tourist attractions are generally located in mountainous areas or at the foothills of mountains, far from residential settlements. Due to their geographical location, tourism managers face difficulties in monitoring environmental conditions and tourist activities. At Curug Dhuwur Waterfall, unpredictable weather changes can cause sudden fluctuations in water quality and water levels, posing safety risks to tourists due to unexpected changes in water flow. Previous studies have mainly focused on monitoring water levels and water quality without integrating tourist activity monitoring into a single system. Therefore, this study aims to design and implement an Internet of Things (IoT)-based early warning and tourist swimming activity monitoring system capable of monitoring water levels and tourist activities in real time to improve visitor safety and support disaster mitigation efforts. The system was developed using the prototyping method and consists of a NodeMCU ESP8266, an ultrasonic sensor, a turbidity sensor, and a laser receiver integrated with a website and Telegram platform. System functionality was evaluated using black-box testing, while user satisfaction was assessed using the System Usability Scale (SUS). The results indicate that the proposed IoT-based system can assist tourism managers in monitoring water conditions and visitor activities more effectively, with an ultrasonic sensor measurement accuracy of 98.33%. The SUS evaluation produced a score within Grade Scale D and the High Acceptability Range, indicating that the system is acceptable for use by tourism managers. In addition, the system successfully delivered monitoring information and warning notifications through both the website and Telegram platform according to the detected conditions. The implementation of the IoT-based monitoring system enables tourism managers to respond more quickly to potential flood hazards and unsafe swimming activities, thereby improving visitor safety and supporting disaster mitigation efforts.